2010
DOI: 10.1183/09031936.00028009
|View full text |Cite
|
Sign up to set email alerts
|

Treprostinil inhibits the recruitment of bone marrow-derived circulating fibrocytes in chronic hypoxic pulmonary hypertension

Abstract: A unique subpopulation of peripheral blood mononuclear cells that exhibit a parallel expression of haematopoietic and mesenchymal markers has been described as ''circulating fibrocytes''. These cells were demonstrated to obtain a fibroblastic phenotype in tissues or cell culture and contribute to pulmonary fibrotic disorders and tissue remodelling processes.The aim of our study was to characterise the recruitment of circulating fibrocytes in vivo in the model of chronic hypoxic pulmonary hypertension in mice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
41
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 48 publications
9
41
2
Order By: Relevance
“…1g). In accordance with NIKAM et al [2], who found rare fibrocytes in only two cases out of 10, both with plexiform lesions, we did not observe fibrocyte accumulation (i.e. cells expressing both CD45 and vimentin) in the perivascular areas of remodelled small pulmonary arteries in the PAH lungs of four samples we analysed (data not shown).…”
Section: To the Editorssupporting
confidence: 72%
See 3 more Smart Citations
“…1g). In accordance with NIKAM et al [2], who found rare fibrocytes in only two cases out of 10, both with plexiform lesions, we did not observe fibrocyte accumulation (i.e. cells expressing both CD45 and vimentin) in the perivascular areas of remodelled small pulmonary arteries in the PAH lungs of four samples we analysed (data not shown).…”
Section: To the Editorssupporting
confidence: 72%
“…Another nonexclusive hypothesis is that the low level of circulating fibrocytes is due to their increased pulmonary vascular recruitment. This hypothesis, raised by FRID et al [5], is not consistent with data obtained in PAH lungs here and by others [2] describing normal fibrocyte cell count in the perivascular areas of small pulmonary arteries. Furthermore, it remains difficult to extrapolate from studies in the hypoxic model of PAH to the human disease, in which lungs are examined at the pulmonary transplantation time-point, after long disease duration.…”
Section: To the Editorscontrasting
confidence: 56%
See 2 more Smart Citations
“…The study of NIKAM et al [31] in the current issue of the European Respiratory Journal provides further support that fibrocytes accumulate in the pulmonary arteries of animals with chronic hypoxic pulmonary hypertension. This work builds on previous studies demonstrating that, in both a large animal model (neonatal calf) and hypoxic rats and mice, fibrocytes accumulate in the perivascular lesions of the vessel wall under chronically hypoxic conditions [29,32].…”
mentioning
confidence: 67%